The Analysis of Firm Size, Asset Tangibility, and Financial‎Performance of Non-Financial Firms Listed on TheNigerian ‎Exchange Limited - Sunday, Odeh O; M, Habibu Sabari; Abiodun , Popoola; Shitu, Isah; Atayi, Abraham Vincent; Evinemi , Elijah Adeiza (International Journal of Accounting and Economics Studies, 2026)
This study examined the effect of asset tangibility, a firm-specific factor, on the financial ‎performance of non-financial firms listed on the Nigerian Exchange Group and assessed the ‎moderating role of firm size. Covering 78 firms across nine industries, including oil and gas, ‎communication, real estate, healthcare, industrial goods, consumer goods, services, and ‎conglomerates, the study spanned the period from 2012 to 2024. Descriptive statistics were ‎employed to summarize the data characteristics, while the cross-sectional dependence ‎augmented IPS (CIPS) test was used to assess stationarity. Additional diagnostic tests, ‎including correlation analysis, slope heterogeneity, heteroscedasticity, and serial correlation, ‎ensured model robustness. The Prais-Winsten regression with panel-corrected standard errors ‎‎(PCSEs) was applied to estimate the long-run effects of the explanatory variables on financial ‎performance. Empirical findings showed that asset tangibility exerted a negative and ‎statistically significant effect on financial performance, suggesting that higher fixed asset ‎intensity reduces profitability. The moderating analysis further revealed that firm size ‎strengthened the relationship between asset tangibility and financial performance, indicating ‎that larger firms can better leverage tangible assets to enhance efficiency and returns. These ‎results highlight the importance of strategic asset allocation and scale efficiency in improving ‎firm performance. The study recommends that firm managers optimize asset structures and ‎pursue growth strategies that exploit size advantages to mitigate inefficiencies linked to ‎excessive asset tangibility and sustain long-term financial performance in Nigeria’s non-‎financial sector‎.